2019
DOI: 10.29133/yyutbd.466037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different PGPR Formulations, Chemical Fertilizers and Their Combinations on Some Plant Growth Characteristics of Poinsettia

Abstract: This study was carried out to determine effects of different PGPR formulations, chemical fertilizers and their combinations on some plant growth characteristics of poinsettia under climate-controlled research greenhouse between July 2015 and July 2017. In the study, rooted cuttings of poinsettia (Euphorbia pulcherrima Willd. ex Klotzsch cv. Christmas Feelings) were used as plant material. The applications were created as formulation 1, formulation 2, formulation 3, formulation 4, the full amount of commonly us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Several studies have shown that the application of PGPR as a biological fertilizer could suppress the usage of inorganic fertilizers on horticultural crops (Parlakova Karagöz & Dursun, 2019;Utami et al, 2017), increase plant growth and its yield (Jumiati & Rosmini, 2021;Mohamed et al, 2019), increase leaf chlorophyll content (Rosida & Nugroho, 2017), reduce farming production costs and create healthy agriculture and its products that are safe for consumption (Susanti et al, 2020). This community service program for the regional superior product schematics is going to train and assist farmers and the community in formulating PGPR and applying it to the shallot plantation area to make it easier for farmers to adopt for its usability on their farms to supporting the development of shallots as a leading commodity in the Central Sulawesi region.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the application of PGPR as a biological fertilizer could suppress the usage of inorganic fertilizers on horticultural crops (Parlakova Karagöz & Dursun, 2019;Utami et al, 2017), increase plant growth and its yield (Jumiati & Rosmini, 2021;Mohamed et al, 2019), increase leaf chlorophyll content (Rosida & Nugroho, 2017), reduce farming production costs and create healthy agriculture and its products that are safe for consumption (Susanti et al, 2020). This community service program for the regional superior product schematics is going to train and assist farmers and the community in formulating PGPR and applying it to the shallot plantation area to make it easier for farmers to adopt for its usability on their farms to supporting the development of shallots as a leading commodity in the Central Sulawesi region.…”
Section: Introductionmentioning
confidence: 99%